Analysis of Nitrogen Dioxide as Air Pollutant in Office, Industrial, Residential, and Transportation Areas in Lampung Province - Agung Abadi Kiswandono; Kharisma Citra Aprilia; Anisa Rahmawati; Rusyda Maulida Khairati; Rinawati Rinawati (JKPK (Jurnal Kimia dan Pendidikan Kimia), 2025)
Monitoring air quality can be undertaken in industrial areas, residential areas, offices, and transportation hubs to maintain public health and sustainable environmental practices in Lampung Province. The province suffers unique challenges, including a mix of emission sources (industrial activities, vehicular traffic, and domestic operations). Industrial zones have high levels of nitrogen dioxide (NO₂) due to manufacturing, transportation hubs have increased NO₂ due to vehicle emissions, and residential regions provide background pollution from household pollutants. Such complex spires must be addressed to achieve acceptable levels of air quality. This research aimed to analyze NO₂ concentrations on four stations in 15 districts of Lampung Province using the Air Pollution Index Values (ISP - Indeks Standar Pencemaran Udara). To assess the coupling relationship between the NO₂ concentrations and seasonal variations over 2 years, Statistical Analysis of Variance (ANOVA) was analyzed. The results showed that NO₂ levels had higher concentrations along transportation routes but were still safe and non-hazardous according to Regulation No. 41 of 1999. The average NO₂ concentrations in the districts were also below the regulatory threshold, reflecting good air quality management in the region. The ANOVA analysis results with the Anderson-Darling test show p-values of 0.322 (rainy season) and 0.258 (dry season), both above the 0.05 significance level. These results imply that the data follows a normal distribution and that there are no significant differences between the districts' average NO₂ concentrations by season. The study highlights the necessity of continued surveillance and targeted interventions to address air quality issues in Lampung Province.